PKM "TRANSFORMASI MELALUI BAHASA: PELATIHAN BAHASA INGGRIS DAN KARAKTER UNTUK ANAK PANTI ASUHAN DHARMA GIRI" - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
The community service program entitled "Transformation Through Language: English and Character Training for Children at Dharma Giri Orphanage" aims to improve the English skills and character development of children at the orphanage. This activity was carried out for six months, attended by 30 children with various age backgrounds and language abilities. The training methods applied included interactive teaching sessions, group discussions, and game activities designed to increase children's motivation and engagement. The evaluation results showed a significant increase in English skills, with the average final quiz score increasing from 60 to 80. In addition, the children also showed positive developments in aspects of character, such as self-confidence and the ability to work together. The active participation of various partners, including orphanage administrators, teachers, volunteers, and donors, has strengthened the success of this program. This program is expected to continue and provide a wider impact on children at Dharma Giri Orphanage, preparing them to face challenges in the future.